THE EFFECT OF TOUR GUIDE KNOWLEDGE AND DESTINATION IMAGE ON CUSTOMER SATISFACTION AT TRAVEL AGENCY IN MAKASSAR - Thomas, Gailyn Josephine; Mangantar, Maryam; Tumewu, Ferdinand (Universitas Sam Ratulangi, 2025)
As competition among tourism destinations increases, providing excellent service quality and building a positive image have become crucial in achieving tourist satisfaction. This study aims to analyze the effect of tour guide knowledge and destination image on customer satisfaction among tourists traveling from a Makassar-based travel agency to North Sulawesi. A quantitative approach was applied using multiple linear regression analysis. Data were collected through questionnaires distributed to tourists who joined tour packages from PT. Vifa Holiday Indonesia. The results show that both tour guide knowledge and destination image have a positive and significant influence on customer satisfaction, with destination image having a greater impact. The study concludes that enhancing tour guide competence and strengthening the destination’s image are essential strategies for improving tourist satisfaction and encouraging repeat visits. Keywords: Tour Guide Knowledge, Destination Image, Customer Satisfaction